2010
DOI: 10.1097/fpc.0b013e32833ccd56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the CYP3A5*3 variant on cyclosporine exposure and acute rejection rate in renal transplant patients: a meta-analysis

Abstract: We concluded that the CYP3A5*3 variant could be associated, to a certain extent, with increased CsA dose-adjusted C0 in blood and reduced mean daily doses, but that this genetic variant allele seemed to have little effect on the acute rejection rate in renal transplant patients taking CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Thus, CsA pharmacokinetic time points and patient ethnicity affected the association between CYP3A5*3C and CsA pharmacokinetics. Furthermore, a metaanalysis suggested that CYP3A5*3 correlates with CsA pharmacokinetics in Asians [23] . An LD has been observed between CYP3A4*1G and CYPE3A5*3C carriers in Asian populations [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CsA pharmacokinetic time points and patient ethnicity affected the association between CYP3A5*3C and CsA pharmacokinetics. Furthermore, a metaanalysis suggested that CYP3A5*3 correlates with CsA pharmacokinetics in Asians [23] . An LD has been observed between CYP3A4*1G and CYPE3A5*3C carriers in Asian populations [24] .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of CYP3A5*3 in 1821 kidney transplant recipients concluded that CYP3A5*3 may have a small effect on cyclosporine pharmacokinetics but is not likely clinically relevant (44). Likewise, a recent review of ABCB1 determined a lack of consistent effect on cyclosporine pharmacokinetics, though it might be important in nephrotoxicity (discussed below) (27).…”
Section: Calcineurin Inhibitors and Pharmacokinetic Phenotypesmentioning
confidence: 99%
“…A summary of these are in Table 2. Acute rejection is commonly investigated, but studies to date have not shown a strong association of pharmacogenes with acute rejection in kidney transplant recipients treated with calcineurin inhibitors, as lately reviewed (13, 44). A recent meta-analysis confirmed that CYP3A5 and ABCB1 have minimal effect on acute rejection in tacrolimus treated patients (24).…”
Section: Calcineurin Inhibitors and Pharmacodynamic Phenotypesmentioning
confidence: 99%
“…The CYP3A5 * 3 allele is associated with reduced CYP3A5 enzyme activity (13). CYP3A5 * 3 has not been shown to be a clinically important in the metabolism of cyclosporine so it was not genotyped in the cyclosporine recipients (14)(15)(16). Pretransplant recipient DNA was isolated from lymphocytes obtained from peripheral blood after RBC lysis, with DNA purity and concentration determined by ultraviolet spectroscopy (Thermo Scientific, Wilmington, DE).…”
Section: Genotyping For Cyp3a5 * 3 In the Tacrolimus Recipientsmentioning
confidence: 99%